STUDY THE IMPACT OF TECHNOLOGY ON TEACHING OF MOTHER TONGUE (PUNJABI) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
Today technology of education is being developed with the aim not only of making education more widely available, but also of improving the quality of education. Practice of teaching is today entering a period of revolution. The teacher of today does not consider the child as a vessel waiting to be filled up with facts, nor as a pliable plastic material which can be transformed into any shape enabling him to project his idea on it but the modern teacher considers each child as a kin to a plant and helps the child to grow according to his abilities and aptitudes. As a result of the impact of educational technology, a few ideas have acquired currency in education, Educational technology implies a behavoural science approach to teaching and learning and it makes use of pertinent scientific and technological aids in its wide sense as understood today, includes the development, application and evaluation of systems, techniques and aids in the field of learning.